The Role of Early Childhood Education in Shaping Children's Character for the Future (Analysis of Character Formation at Sekar Pelangi Kencana PAUD, Paoman Village, Indramayu) - Tri Maulana Yusuf (Mazidah: Journal Of Educational Research, 2025)
Early Childhood Education (PAUD) plays a central role in shaping children's character through a structured learning process from an early age. This study aims to examine how early childhood education can contribute to the formation of children's character, moral values, and social behavior for the future. The method used was a literature review, reviewing various scientific sources related to PAUD and character education, and conducting direct observations, interviews, and documentation at the PAUDs studied. The results indicate that integrated character education in PAUD can improve children's social skills, communication, empathy, and cooperation, contributing to character development. Synergy between family, school, and the community is essential for optimal character formation. This study emphasizes the importance of strengthening character education from an early age as a foundation for developing a generation with strong character and global competitiveness in the future.